Chromatin binding of the fission yeast replication factor mcm4 occurs during anaphase and requires ORC and cdc18 - Kearsey, Stephen E. (Oxford University Press, 2000)
We describe an in situ technique for studying the chromatin binding of proteins in the fission yeast Schizosaccharomyces pombe. After tagging the protein of interest with green fluorescent protein (GFP), chromatin-associated protein is detected by GFP fluorescence following cell permeabilization and washing with a non-ionic detergent. Cell morphology and nuclear structure are preserved in this procedure, allowing structures such as the mitotic spindle to be detected by indirect immunofluorescence. Cell cycle changes in the chromatin association of proteins can therefore be determined from individual cells in asynchronous cultures. We have applied this method to the DNA replication factor mcm4/cdc21, and find that chromatin association occurs during anaphase B, significantly earlier than is the case in budding yeast. Binding of mcm4 to chromatin requires orc1 and cdc18 (homologous to Cdc6 in budding yeast). Release of mcm4 from chromatin occurs during S phase and requires DNA replication. Upon overexpressing cdc18, we show that mcm4 is required for re-replication of the genome in the absence of mitosis and is associated with chromatin in cells undergoing re-replication.